라이프스타일에 따른 도시농업 유형 선호도 분석 - 이동관; Lee Dong-gwan; 조세환; Cho Se-hwan (한국조경학회지, 2016)
본 연구는 라이프스타일에 따른 도시농업 유형 선호도를 분석함으로써 향후 『도시농업활성화 정책』 수립을 위한 기초 자료를 제시하는데 목적이 있다. 연구방법은 서울특별시 자치구 중 도시농업 활성화를 지원할 수있는 근거를 마련한 9개자치구민을 대상으로 설문조사를 실시하였다. 이를 통해 라이프스타일과 도시농업 선호활동과의 인과관계를 검정하고자 하였다. 연구결과, 첫째, `건강추구형`이 도심형 도시농업에 유의한 것으로 나타났다. 이는 안전한 먹거리와 건강을 추구하는 도시민이 도시농업 교육 프로그램에 적극적으로 참여하고, 도심 내 자연경관 향상을 위해 식물 및 경관작물 심기, 도시농업박람회 참가 등의 도심형 도시농업활동을 선호하는 것으로 나타났다. 둘째, `여가활동형`이 주택활용형 도시농업에 유의한 것으로 나타났다. 주로 취미 및 여가활동을 중시하는 도시민은 실내 생활 속에 텃밭 가꾸기, 아파트 베란다 공간을 활용한 텃밭 가꾸기 등 주로 텃밭 가꾸기 등의 주택활용형도시농업 활동을 선호하는 것으로 나타났다. 셋째, `건강추구형`이 학교교육형 도시농업과, 농장 및 공원형 도시농업에 유의한 것으로 나타났다. 건강을 추구하는 도시민은 교육농장 참여 및 학교텃밭 가꾸기, 도심 외곽 개인 농장 운영, 도시농업 박람회 참가 등의 참여 활동을 선호하는 것으로 나타났다. 넷째, `가족지향형`이 학교교육형 도시농업에 유의한 것으로 나타났다. 가족지향형 도시민은 학교와 연계된 다양한 도시농업 교육 및 활동에 적극 참여하는 활동을 선호하는 것으로 나타났다. 본 연구는 도시농업 유형을 고찰하고, 라이프스타일과 도시농업 유형 선호도와의 영향관계를 살펴, 도시농업의 실수요자의 성향 및 선호활동을 알아보는데 연구의 의의가 있다. The objective of this study is to suggest basic data for establishing future urban agriculture vitalization policies, by analyzing the preference of urban agriculture types in accordance with lifestyle as the standard of living for urban residents is improved. A survey was conducted targeting residents of nine autonomous regions that have established grounds for supporting the urban agriculture vitalization by enacting an urban agriculture ordinance, among 25 autonomous regions of Seoul. It aimed to verify a causal relationship between lifestyle and preferred activity of urban agriculture. In the results of the study first, a `Health pursuit-type` was significant within the `urban type` urban agriculture. These urban residents, pursuing safe food and health, actively participated in urban agriculture educational programs, and also preferred urban agricultural activities such as planting plants, landscape crops for the improvement of natural scenery in the downtown, and also participating in urban agriculture fairs. Second, `Leisure activity-type` was significant with the `House advantage type` urban agriculture. Urban residents mostly emphasizing hobby and leisure activities preferred the `House advantage type` urban agricultural activities such as tending a vegetable garden in indoor life or using the veranda space of an apartment. Third, `Health pursuit-type` was significant with the `Schooling type` urban agriculture and `Farm and Park type` urban agriculture. Urban residents pursuing health preferred tending an educational-type vegetable garden and educational farm connected to schools, running private farms outside of the downtown, and actively participating in urban agriculture park. Fourth, `The neighborhood type` was significant with the `Schooling type` urban agriculture. `The neighborhood type` urban residents preferred actively participating in diverse urban agriculture education activities. The significance of this study is to examine the tendency and preferred activities of end users of urban agriculture by suggesting the necessity of viewing urban agriculture from the aspect of a consumer, and then examining the influential relationship between lifestyle and preference of urban agriculture-types.